CLINICAL FEATURES, RISK FACTORS, AND THERAPEUTIC APPROACHES IN AGE-RELATED MACULAR DEGENERATION (AMD) - Yusupov Mirza Murodovich (World Scientific Research Journal, 2025)
Annotation: Age-related macular degeneration (AMD) is one of the leading causes of irreversible vision loss in individuals over 50 years of age in developed countries. It primarily affects the macula, the central region of the retina responsible for sharp, detailed vision. AMD is typically categorized into two forms: dry (atrophic) and wet (neovascular or exudative). The dry form is more common and progresses slowly, while the wet form is less prevalent but more severe and can lead to rapid vision loss. This article explores the clinical features, risk factors, diagnostic tools, and treatment strategies for AMD. Utilizing a structured methodological approach, it evaluates patient data, imaging results, and treatment outcomes across various stages of the disease. The findings emphasize the role of early diagnosis and the application of anti-VEGF therapies and lifestyle interventions in managing AMD progression and preserving visual function.